2020
DOI: 10.3390/w12061800
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Monitoring with Moss-Bag and Mussel Transplants in Reservoirs

Abstract: For the first time, transplants with moss-bags and mussels together were applied to study the water quality in standing water bodies. The tested species: Fontinalis antipyretica Hedw. and Sinanodonta woodiana (Lea, 1834) were collected from unpolluted sites and analyzed to obtain background levels. Then, the moss and mussels were left in cages for a period of 30 days in three reservoirs where both are not present naturally. Two of the reservoirs suffer from old industrial contamination and one is affected by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…Increased number of cells and decreased cell size, mainly in width, was registered in Fontinalis antipyretica exposed at all three reservoirs. The tested micromorphological biomarkers showed response in conditions of heavy contamination with Al, As, Cd, Cr, Ni and Pb (Kardzhali Reservoir), with Al, Cd, Cr, Cu and Pb (Studen Kladenets Reservoir), with SCCPs (Zhrebchevo Reservoir) and PBDEs in all three reservoirs [ 24 ]. Nevertheless, the most pronounced was the alteration in the above biomarkers in the moss samples from Zhrebchevo Reservoir, which could be linked with the assessed short-chain chlorinated paraffins (SCCPs) in water above the EQS and a maximum of 9.2 µg kg −1 accumulated in the moss-bags.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased number of cells and decreased cell size, mainly in width, was registered in Fontinalis antipyretica exposed at all three reservoirs. The tested micromorphological biomarkers showed response in conditions of heavy contamination with Al, As, Cd, Cr, Ni and Pb (Kardzhali Reservoir), with Al, Cd, Cr, Cu and Pb (Studen Kladenets Reservoir), with SCCPs (Zhrebchevo Reservoir) and PBDEs in all three reservoirs [ 24 ]. Nevertheless, the most pronounced was the alteration in the above biomarkers in the moss samples from Zhrebchevo Reservoir, which could be linked with the assessed short-chain chlorinated paraffins (SCCPs) in water above the EQS and a maximum of 9.2 µg kg −1 accumulated in the moss-bags.…”
Section: Discussionmentioning
confidence: 99%
“…The selected reservoirs are affected by a different degree of pollution [ 24 ]. Kardzhali (41.638475° N, 25.304432° E WGS 84) and Studen Kladenets (41.622244° N, 25.441933° E WGS 84) reservoirs suffer from old industrial contamination and have sediments’ loads of priority substances (e.g., Cd and Pb).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into different types of fish has shown that heavy metals can lead to changes in the physiological activity and biochemical parameters of various tissues of these organisms [2,[7][8][9]. Heavy metals pose a risk to aquatic ecosystems due to their bioaccumulation.…”
mentioning
confidence: 99%